基于速度图解法优化分析拉维娜式行星齿轮变速器的传动方案 - 张玉书; 岳东鹏 (Jixie chuandong)
Using the special form of dual planetary gear mechanism superseding its general form is proposed to optimize the movement analysis of Ravigneaux planetary gear transmission.The velocity graphic method is used to analyze the typical transmission scheme and vector diagram of every case following is drawn through following the describing basic principles.The correctness of the optimization method is verified by comparing the transmission ratio calculated by velocity graphic method and analytic method respectively.